2018
DOI: 10.1080/10590501.2019.1555323
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons as a potential source of carcinogenicity of mate

Abstract: Drinking mate, an infusion of the herb ilex paraguariensis, is very common in several South American countries, and has been associated with an increased risk of esophageal cancer. This increased risk may be attributed to drinking mate very hot, or to mate’s potentially carcinogenic contaminants, such as polycyclic aromatic hydrocarbons (PAHs). Mate leaves are often dried via smoking, and therefore commercial samples may have high amounts of PAHs. We found 10 original articles that had measured PAHs in commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…Mate was found to contain N-nitroso, polycyclic aromatic hydrocarbons (PAH), and other substances which are carcinogenic substances. 30 PAH was found to raise the risk for childhood leukaemia. PAH exposure can be from parental exposure to vehicle exhaust, 31 paternal smoking, [24][25] and hookah which was found to have 16 components of PAH.…”
Section: Tobacco and Dietmentioning
confidence: 99%
“…Mate was found to contain N-nitroso, polycyclic aromatic hydrocarbons (PAH), and other substances which are carcinogenic substances. 30 PAH was found to raise the risk for childhood leukaemia. PAH exposure can be from parental exposure to vehicle exhaust, 31 paternal smoking, [24][25] and hookah which was found to have 16 components of PAH.…”
Section: Tobacco and Dietmentioning
confidence: 99%
“…Numerous studies have shown significant differences in the total PAHs content ranging from 194 ng/g to 9001 ng/g of dried Yerba Mate leaves. On the other hand, the concentration of benzo[α]pyrene is considered to be the main human carcinogen ranging from 0-603 ng/g of dry material (known permissible levels of this compound in food are 0.001-0.01 mg/kg fresh weight), while for water extracts from of Yerba Mate were extracted at most 10% of this compound [90]. The different content of benzo[α]pyrene in Yerba Mate infusions may result from differences in the PAHs content in the dried raw material and in the procedures used to prepare infusions, such as the ratio of dry leaves to water, water temperature, and/or infusion duration [91].…”
Section: Potential Toxicity Of Yerba Matementioning
confidence: 99%
“…Although mate is traditionally consumed in South America, it is very popular in Syria. Mate was found to contain N-nitroso, polycyclic aromatic hydrocarbons (PAH), and other substances which are carcinogenic substances [29].…”
Section: Potential Factorsmentioning
confidence: 99%